No accelerated arterial aging in relatively young women after preeclampsia as compared to normotensive pregnancy - Janssen, Emma B. N. J.; Hooijschuur, Mieke C. E.; Lopes van Balen, Veronica A.; Morina-Shijaku, Erjona; Spaan, Julia. J.; Mulder, Eva G.; Hoeks, Arnold P.; Reesink, Koen D.; van Kuijk, Sander M. J.; van't Hof, Arnoud; van Bussel, Bas C. T.; Spaanderman, Marc E. A.; et al. (Frontiers in Cardiovascular Medicine, 2022)
Introduction Preeclampsia, an endothelial disorder of pregnancy, predisposes to remote cardiovascular diseases (CVD). Whether there is an accelerated effect of aging on endothelial decline in former preeclamptic women is unknown. We investigated if the arterial aging regarding endothelial-dependent and -independent vascular function is more pronounced in women with a history of preeclampsia as compared to women with a history of solely normotensive gestation(s). Methods Data was used from the Queen of Hearts study (ClinicalTrials.gov Identifier NCT02347540); a large cross-sectional study on early detection of cardiovascular disease among young women (≥18 years) with a history of preeclampsia and a control group of low-risk healthy women with a history of uncomplicated pregnancies. Brachial artery flow-mediated dilation (FMD; absolute, relative and allometric) and sublingually administered nitroglycerine-mediated dilation (NGMD; absolute and relative) were measured using ultrasound. Cross-sectional associations of age with FMD and NGMD were investigated by linear regression. Models were adjusted for body mass index, smoking, antihypertensive drug use, mean arterial pressure, fasting glucose, menopausal state, family history of CVD and stress stimulus during measurement. Effect modification by preeclampsia was investigated by including an interaction term between preeclampsia and age in regression models. Results Of the 1,217 included women (age range 22–62 years), 66.0% had a history of preeclampsia and 34.0% of normotensive pregnancy. Advancing age was associated with a decrease in relative FMD and NGMD (unadjusted regression coefficient: FMD: −0.48%/10 years (95% CI:−0.65 to −0.30%/10 years), NGMD: −1.13%/10 years (−1.49 to −0.77%/10 years)) and increase in brachial artery diameter [regression coefficient = 0.16 mm/10 years (95% CI 0.13 to 0.19 mm/10 years)]. Similar results were found when evaluating FMD and NGMD as absolute increase or allometrically, and after confounder adjustments. These age-related change were comparable in former preeclamptic women and controls (p-values interaction ≥0.372). Preeclampsia itself was independently associated with consistently smaller brachial artery diameter, but not with FMD and NGMD. Conclusion In young- to middle-aged women, vascular aging in terms of FMD and NGMD was not accelerated in women after preeclampsia compared to normotensive pregnancies, even though former preeclamptic women consistently have smaller brachial arteries.